Physiologically Based Pharmacokinetic Modeling of Palbociclib. (22nd August 2016) - Yu, Yanke; Loi, Cho‐Ming; Hoffman, Justin; Wang, Diane
Abstract: Palbociclib is an orally available CDK4/6 inhibitor. In humans, palbociclib undergoes metabolism mediated primarily by CYP3A and SULT2A1, and it is also a weak time‐dependent CYP3A inhibitor. The objectives of the current study are to (1) develop a physiologically based pharmacokinetic (PBPK) model of palbociclib based on the in silico, in vitro, and in vivo pharmacokinetic data of palbociclib, (2) verify the PBPK model with clinical drug‐drug interaction (DDI) results of palbociclib with strong CYP3A inhibitor (itraconazole), inducer (rifampin), and a sensitive CYP3A substrate (midazolam), and (3) predict the DDI risk of palbociclib with moderate/weak CYP3A inhibitors. The developed PBPK model adequately described the observed pharmacokinetics of palbociclib after administration of a single oral or intravenous dose of palbociclib. The model‐predicted DDIs of palbociclib with itraconazole, rifampin, and midazolam were consistent with the observed DDIs, with the discrepancies of the predicted vs observed AUCR and Cmax R within 20%, except for the AUC ratio of palbociclib with coadministration of rifampin. Using this final PBPK model, it was predicted that weak CYP3A inhibitors (fluoxetine and fluvoxamine) are anticipated to have negligible DDI risk with palbociclib, whereas moderate CYP3A inhibitors (diltiazem and verapamil) may increase plasma palbociclib AUC by ∼40%. A moderate CYP3A inducer (efavirenz) may decrease plasma palbociclib AUC by ∼40%. The established model is considered sufficiently robust for other applications in support of the continued development for palbociclib.